A representação das mulheres afegãs refugiadas na mídia brasileira: uma análise da cobertura midiática da operação nós por elas - Marinho, Alexandra Guida (2023)
This dissertation has as object of study the media representation of Afghan refugee women in Brazilian journalism. The objective of the research is to understand how the representation of these people is constructed within the journalistic coverage of the Nós Por Elas project, which offered humanitarian visas to seven Afghan judges to live as refugees in Brazil. Based on a theoretical framework that covered gender, migration, communication, journalism and representation based on a qualitative methodology based on content analysis, we analyzed 21 journalistic articles that covered the Nós Por Elas project, with the aim of understanding how the the media constructs the representation of the Afghan refugee woman, as well as the role of journalism in shaping the given social reality related to gender relations and female migration. The work was also guided by three specific objectives, to reflect on how the voices of Afghan women were contemplated in the analyzed corpus, which dimensions of the gender marker were (in)visible and to identify the existence of gender stereotypes related to the world Muslim in this representation. As a result of the analysis, we verified the existence of a journalism still based on abyssal thinking that follows the logic of modern-positivist scientism and that operates ensuring the maintenance of hegemonic social relations. Specifically on the representation of Afghan refugee women, we highlight some research results such as: the westernized look, the confiscation of the speech of Afghan judges, the association of these women with hegemonic gender roles and the stereotyping of Muslim women as passive victims and oppressed by their own culture .